The Degree of Study and Productivity of Soils of Syrdarya and Jizzakh Region Some Ways to Restore - Muxammad Ismatullayevich Umarov; Ro'zmatova Sevinch Baxtiyor qizi; Sultonmurodova E’zozabonu Dilsgod qizi; Sharofiddinova Umida Sharofiddin qizi (Web of Journals Publishing, 2023)
In this article you will get acquainted with preliminary scientific research conducted in the regions of Syrdarya and Jizzakh regions, as well as the results of various deflationary monitoring processes in the fight against wind erosion, reducing the impact of wind force on the soil, and irrigated lands in the region. The results of the experiment suggested planting protective crops to restore the fertility of deflated soils.